Regularities in vertical saccadic metrics: new insights, and future perspectives - Greene, Harold H.; Diwadkar, Vaibhav A.; Brown, James M. (Frontiers in Psychology, 2023)
Introduction Asymmetries in processing by the healthy brain demonstrate regularities that facilitate the modeling of brain operations. The goal of the present study was to determine asymmetries in saccadic metrics during visual exploration, devoid of confounding clutter in the visual field. Methods Twenty healthy adults searched for a small, low-contrast gaze-contingent target on a blank computer screen. The target was visible, only if eye fixation was within a 5 deg. by 5 deg. area of the target’s location. Results Replicating previously-reported asymmetries, repeated measures contrast analyses indicated that up-directed saccades were executed earlier, were smaller in amplitude, and had greater probability than down-directed saccades. Given that saccade velocities are confounded by saccade amplitudes, it was also useful to investigate saccade kinematics of visual exploration, as a function of vertical saccade direction. Saccade kinematics were modeled for each participant, as a square root relationship between average saccade velocity (i.e., average velocity between launching and landing of a saccade) and corresponding saccade amplitude (Velocity = S*[Saccade Amplitude]0.5). A comparison of the vertical scaling parameter (S) for up- and down-directed saccades showed that up-directed saccades tended to be slower than down-directed ones. Discussion To motivate future research, an ecological theory of asymmetric pre-saccadic inhibition was presented to explain the collection of vertical saccadic regularities. For example, given that the theory proposes strong inhibition for the releasing of reflexive down-directed prosaccades (cued by an attracting peripheral target below eye fixation), and weak inhibition for the releasing of up-directed prosaccades (cued by an attracting peripheral target above eye fixation), a prediction for future studies is longer reaction times for vertical anti-saccade cues above eye fixation. Finally, the present study with healthy individuals demonstrates a rationale for further study of vertical saccades in psychiatric disorders, as bio-markers for brain pathology.